Biological and environmental influences on the migration phenology of Atlantic salmon Salmo salar smolts in a chalk stream in southern England. (9th June 2021) - Simmons, Olivia M.; Gregory, Stephen D.; Gillingham, Phillipa K.; Riley, William D.; Scott, Luke J.; Britton, J. Robert
Abstract: Migration enables animals to access important resources throughout their lifetime but exists in a trade‐off with elevated mortality risk. In spring, juvenile Atlantic salmon ( smolts ) migrate from their natal rivers for marine feeding grounds, with the timing of their marine entry a potentially important determinant of their long‐term survival. However, there is relatively little known on how the interaction of biological and environmental factors affect smolt migration phenology at the individual level, and how these vary throughout the duration of the smolt seaward migration ( run ). Using 15‐year tag, recapture, and detection datasets of individual smolts (marked with passive integrated transponder tags) from a chalk stream in southern England, the influences of a range of biological and environmental variables were tested on the run timing of individual smolts, measured as the timing of their arrival in a lower river reach. The probability of smolts arriving earlier in the lower river reach was elevated following winters that were relatively warm, and when there were larger positive daily changes in water temperature and discharge during the run. Early migrants tended to be larger individuals and from sites lower in the catchment, from where the smolts had to migrate relatively shorter distances. Later migrants were more likely to migrate in schools, but with schooling behaviour also more likely to occur during daylight than at night. The relative influence of some of these variables altered throughout the run. Relative changes in daily water temperature were not important during the middle period of the smolt run but were important at the start and end of the run. Relative changes in daily discharge were most influential towards the end of the run, when even relatively small changes in discharge had a strong influence on migration. These results reveal the importance of a wide range of biological and environmental variables on the phenology of smolt migrations, and how their influence can alter throughout the run. With predictions of annually increasing river temperatures, more frequent and intense discharge events, and associated shifts to earlier migration, these results emphasise that such changes in climate are likely to have substantial consequences on the future success of smolt migrations and thereby future numbers of returning adult spawners.